2012
DOI: 10.1136/heartjnl-2012-302505
|View full text |Cite
|
Sign up to set email alerts
|

Successful transcatheter aortic valve implantation (TAVI) is associated with transient left ventricular dysfunction

Abstract: Objective To investigate early haemodynamic changes after transfemoral transcatheter aortic valve implantation (TAVI) and the relationship with myocardial injury and neurohormonal activation. Design Single-centre prospective observational study. Setting Tertiary cardiac centre. Patients 42 patients undergoing transfemoral TAVI were included in this study. Main outcome measures Haemodynamic measurements and echocardiography-derived indices characterising myocardial function were recorded at baseline, 6 and 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Our group have previously shown that even successful TAVI is linked with transient left ventricular dysfunction 39. RDW is an independent predictor of mortality in patients with acute heart failure,40 but further studies are needed to clarify whether RDW correlates with the extent of such procedural haemodynamic changes in the setting of TAVI.…”
Section: Discussionmentioning
confidence: 97%
“…Our group have previously shown that even successful TAVI is linked with transient left ventricular dysfunction 39. RDW is an independent predictor of mortality in patients with acute heart failure,40 but further studies are needed to clarify whether RDW correlates with the extent of such procedural haemodynamic changes in the setting of TAVI.…”
Section: Discussionmentioning
confidence: 97%
“…Published and unpublished data from our own group also show that this inflammatory response is significantly higher in patients undergoing transapical procedures 11. In this context it is interesting to know that TEA inhibits intraoperative cortisol as well as catecholamine surge and reduces inflammatory response after cardiopulmonary bypass surgery 12.…”
mentioning
confidence: 88%
“…A recent study has shown that there is transient systolic and diastolic dysfunction within the first 24 h of a successful TAVR 51. This is associated with an increase in serum markers of myocardial injury and dysfunction suggesting that the post-procedural dysfunction is due to myocardial stunning and periprocedural injury to the myocardium.…”
Section: Aortic Valve Interventionsmentioning
confidence: 99%